Evaluasi Aktivitas Antioksidan dan Antibakteri Dari Daun Empat Tumbuhan Suku Baduy Sebagai Sumber Bahan Alam Potensial - Permatasari, Vera; Riskiana, Angger Arfi; Saefurohman, Asep; Prastya, Muhammad Eka; Ridha, Rafifa; Primahana, Gian; Dewijanti, Indah Dwiatmi (Jurnal Sumberdaya Hayati, 2025)
Baduy indigenous plants have great potential as natural sources of bioactive compounds, yet scientific studies on their biological activities remain limited. This study aimed to evaluate the antioxidant, antibacterial activities, and total phenolic content of the leaves from four Baduy plant species: Gardenia jasminoides, Strobilanthes crispus, Ficus callosa, and Artocarpus camansi. The leaves were extracted with methanol, followed by fractionation using n-hexane and ethyl acetate. Antioxidant activity was assessed using DPPH and ABTS assays, total phenolic content was determined by the Folin–Ciocalteu method, and antibacterial activity was tested against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Escherichia coli using the broth dilution method to determine Minimum Inhibitory Concentration (MIC). The results showed that the ethyl acetate fraction of A. camansi leaves exhibited the highest total phenolic content (23.53 mg GAE/g extract). This fraction demonstrated strong antioxidant activity in the ABTS assay (IC50 = 18.55 ppm) and moderate activity in the DPPH assay (IC50 = 50.67 ppm). Moreover, it showed strong antibacterial activity against S. aureus, B. subtilis, and P. aeruginosa. These findings indicate that A. camansi leaves possess promising potential as a natural source of antioxidant and antibacterial agents.